2011
DOI: 10.1016/j.aim.2011.05.015
|View full text |Cite
|
Sign up to set email alerts
|

The isomorphism problem for some universal operator algebras

Abstract: This paper addresses the isomorphism problem for the universal (nonself-adjoint) operator algebras generated by a row contraction subject to homogeneous polynomial relations. We find that two such algebras are isometrically isomorphic if and only if the defining polynomial relations are the same up to a unitary change of variables, and that this happens if and only if the associated subproduct systems are isomorphic. The proof makes use of the complex analytic structure of the character space, together with so… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
124
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 61 publications
(129 citation statements)
references
References 33 publications
(46 reference statements)
5
124
0
Order By: Relevance
“…As an operator algebra concretely represented on a reproducing kernel Hilbert space, M V also has the weak-operator topology (wot). In [16,Lemma 11.9] we observed that, as is the case for the free semigroup algebras L d [13], the weak-operator and weak- * topologies on M V coincide. The setting there was slightly different, but the proof remains the same.…”
Section: The Character Space Of M Vmentioning
confidence: 99%
See 4 more Smart Citations
“…As an operator algebra concretely represented on a reproducing kernel Hilbert space, M V also has the weak-operator topology (wot). In [16,Lemma 11.9] we observed that, as is the case for the free semigroup algebras L d [13], the weak-operator and weak- * topologies on M V coincide. The setting there was slightly different, but the proof remains the same.…”
Section: The Character Space Of M Vmentioning
confidence: 99%
“…In [16], now improved by [20], we saw that in the case of homogeneous varieties V and W , the algebras A V and A W are isomorphic if and only if the algebras M V and M W are isomorphic. The above discussion shows that this is not true in general.…”
Section: The Norm Closed Algebras a Vmentioning
confidence: 99%
See 3 more Smart Citations